PEMANFAATAN TEKNOLOGI DIGITAL DAN EFESIENSI PELAPORAN SIWASLU DALAM KINERJA BAWASLU DI KABUPATEN KEBUMEN - Mohammad Maskur; Blandina Hendrawardani (JURNAL ILMIAH EDUNOMIKA, 2025)
The digital transformation of election monitoring and reporting systems has become a critical need to enhance the effectiveness and efficiency of the General Election Supervisory Agency (Bawaslu). This study aims to analyze the influence of digital technology utilization and the efficiency of SIWASLU reporting on Bawaslu's monitoring performance in Kebumen Regency. Using a quantitative approach and explanatory method, this study involved 155 respondents consisting of Panwascam, PKD, and PTPS members in Alian District. Data were analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method with the SmartPLS 3.0 application. The results indicate that digital technology utilization and SIWASLU reporting efficiency have a positive and significant effect on Bawaslu's performance. The R² value of 0.664 indicates that the two independent variables explain 66.4% of the variation in Bawaslu's performance. This study recommends optimizing the use of digital technology in reporting and enhancing human resource capacity to strengthen digital-based election supervision systems at the regional level.Keywords : community empowerment, individual roles, community roles, power, education Keywords: Digital Technology, Reporting Efficiency, SIWASLU, Bawaslu Performance, Election Monitoring